Digital restitution of expropriated heritage: technological modes of experience (Itinera, 2024)
For more than a century now, Western museological institutions have been exhibiting expropriated heritage across their museum spaces, curating displays which conveyed prescriptive epistemic paradigms, informed by a rigidly imposed notion of primitive aesthetic. As the restitution of physical heritage is at the center of the international political debate, both museums and artists have started to employ digital technologies to engage with the looted heritage, envisioning new paths for access and experience, through projects which aspire to question traditional narratives. Interestingly, digital technologies offer the opportunity to mobilize a very rigid state of affairs, overcoming diplomatic stances and shifting the debate towards questions of identity, values and aesthetics. This paper intercepts the digital repatriation phenomenon, analyzing two case studies which relate to the Benin Bronzes: the international cooperative institutional programme Digital Benin and the AI generated work Igùn (2020) by artist Minne Atairu. These two projects, in their own media specific ways, create new modes of experience to interact with the Benin Kingdom heritage, operating at the intersection between research, display, creativity and meaning making. As the digital restitution debate becomes more and more pressing in the current scenario, the research offers an analysis of how digital technologies can be used to foster new paths to engage with expropriated heritage, overcoming rigid definitions of knowledge.
Keywords: Digital Restitution, Benin Bronzes, Museums, Digital Technologies.